Phonological Acquisition of Indonesian in Two-Year-Old Children in Magelang City - Zidan Rizka Alhafidz; Latifatuzzahro Latifatuzzahro; Amalia Hilda Saputri; Erawati Erawati (CV Projurnal Mitra Publikasi, 2025)
The critical period of phonological development in early childhood, where pronunciation errors can impact communication and subsequent language skills, serves as the background for this research. This research explores phonological acquisition in 2-year-old children in the city of Magelang in a study of the Indonesian language. The primary objective is to identify and describe the specific phonological patterns, including the mastery of vowels and consonants, and the common simplifications or errors present in their speech. The observational method involves data collection through recording children’s conversations in their natural home environments, which were then transcribed and analyzed for phonetic and phonological features. The research results indicate individual variations in phonological acquisition, identifying developmental patterns and differences influenced by the environment. Key findings reveal that while vowel sounds are generally acquired early, significant variation exists in the production of consonants, with certain phonemes like /r/ and /s/ often being substituted or omitted. The study also highlights the strong influence of the local Magelang dialect and parental input on the children’s emerging sound systems. Phonological analysis is conducted to understand changes in sound usage, vocabulary development, and the role of social interaction in shaping correct speech patterns. This study contributes to the understanding of phonological acquisition in the Indonesian language among preschool children, with practical implications for the development of educational strategies and interventions in Magelang city. In conclusion, the research underscores the interplay between universal developmental sequences and environmental factors in shaping early phonological competence.